2007
DOI: 10.1021/ol070753r
|View full text |Cite
|
Sign up to set email alerts
|

IPy2BF4-Mediated Transformation of n-Pentenyl Glycosides to Glycosyl Fluorides:  A New Pair of Semiorthogonal Glycosyl Donors

Abstract: Bis(pyridinium) iodonium(I) tetrafluoroborate (IPy2BF4), a solid and stable reagent, can be used to transform n-pentenyl orthoesters (NPOEs) and n-pentenyl glycosides (NPGs) into glycosyl fluorides. The latter pair constitutes a new set of semiorthogonal glycosyl donors that can be used in glycosylation strategies, alone or in combination with NPOEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…33 Likewise, we reported a related, albeit less flexible, semiorthogonal approach using S -ethyl vs O -pentenyl, 34 which was extended to fluoride vs O -pentenyl by Fraser-Reid and Lopez. 35 …”
Section: Resultsmentioning
confidence: 99%
“…33 Likewise, we reported a related, albeit less flexible, semiorthogonal approach using S -ethyl vs O -pentenyl, 34 which was extended to fluoride vs O -pentenyl by Fraser-Reid and Lopez. 35 …”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that n -pentenyl glycosides can be selectively activated over glycosyl fluoride acceptors (vide infra). 88 More recently, Hotha et al observed that n -pentenyl glycoside 84 could be activated over propargyl glycosyl acceptor 85 in the presence of NIS/TMSOTf (Scheme 18b). 89 …”
Section: Selective Activationmentioning
confidence: 99%
“…135 Lopez et al reported that n -pentenyl 1,2-orthoesters are activated over glycosyl fluoride acceptors in the presence NIS and Yb(OTf) 3 . 88 Recently, Hotha et al reported that n -pentenyl 1,2-orthoester 139 can be selectively activated over propargyl glycoside 85 in the presence of NIS/Yb(OTf) 3 (Scheme 27b). 89 Along similar lines, propargyl 1,2-orthoester 141 can be selectively activated over n -pentenyl acceptor 142 in the presence of AuBr 3 leading to trisaccharide 143 (Scheme 27c).…”
Section: Selective Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…A very promising orthogonality was shown for O- pentenyl versus O- propargyl glycosides by Hotha et al [17] and for S- glycosyl O- methyl phenylcarbamothioate (SNea) versus thioglycosides/thioimidates by us [18], but still their applicability to multistep synthesis remains to be proven. Working to expand this concept, our group reported a related, albeit less flexible, semiorthogonal approach with the use of S- ethyl and O- pentenyl leaving groups [19], which was later extended to fluoride/ O- pentenyl combination by Fraser-Reid and Lopez [20]. Oxygen- [21] and sulfur-based [22] leaving groups fit into many expeditious strategies for oligosaccharide synthesis [6].…”
Section: Introductionmentioning
confidence: 99%